Diagnosis and Treatment of Cerebral Venous Thrombosis: A Review - Luo, Yaxi; Tian, Xin; Wang, Xuefeng (Frontiers in Aging Neuroscience, 2018)
Abstract: Cerebral venous thrombosis (CVT), also called cerebral venous sinus thrombosis (CVST), is a cerebrovascular disease with diverse clinical manifestations that often affects young adults, women of childbearing age and children. It’s most common clinical manifestations are headache, seizures, altered consciousness and neurological focal signs on physical examination. CVT can manifest as a single symptom, or it can present as a syndrome consisting of multiple symptoms. This non-specific clinical picture makes diagnosing CVT difficult. Although the mortality rate of CVT has been significantly reduced by improvements in treatment and diagnostic techniques, the mortality rate of severe CVT remains as high as 34.2%. Survivors of this type of CVT have varying degrees of residual symptoms and are not able to return to their previous work. Hence, we performed a comprehensive literature search in the PubMed, EMBASE and Medline databases to review the diagnosis and treatment of CVT.